LACKING MANNERS AMONG TERTIARY STUDENTS IN MALAYSIA FOLLOWING THE MOVEMENT CONTROL ORDER - Surina Nayan; Nor Azira Mohd Radzi; Majdah Chulan; Azhar Abdul Rahman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This conceptual paper is on lacking manners among tertiary students in Malaysia following the Movement Control Order (MCO). The MCO has had an undeniably profound effect on students, with many now having to switch to online learning and forgoing their usual routines and interactions with peers. Unfortunately, some students have been struggling to adjust to the new normal, and this has led to a lack of manners among the younger generation. The MCO has caused huge disruption to their lives, and this can lead to a lack of respect for authority figures and a general lack of courtesy. Some students have been observed using inappropriate language, speaking disrespectfully to teachers, and failing to show consideration for others. Parents and teachers need to address these issues as soon as possible and remind students of the importance of good manners. Parents should ensure that their children understand the importance of treating others with respect and showing consideration for those around them. Teachers should also ensure that their students understand the consequences of their actions and the importance of maintaining a positive attitude. Parents and teachers should also focus on the importance of communication and actively encourage students to talk about their feelings and concerns. Finally, it is important to remember that the MCO will eventually come to an end and that students will once again be able to attend school and interact with their peers. Until then, parents and teachers should continue to do their best to ensure that students maintain good manners and continue to uphold the values of respect and courtesy.